The Impact of Operational Efficiency and Risk Management on Good Corporate Governance and its Implications on Company Profitability as a Moderating Variable at BPR Artatama Sejahtera, South Jakarta - Murni Ardina Pandiangan; Cecep Taufiqurrochman; Tatang S Herisman (Green Publisher Indonesia, 2026)
This research aims to analyze the effect of operational efficiency and risk management on Good Corporate Governance (GCG), as well as the effect of GCG on corporate profitability at BPR Artatama Sejahtera, South Jakarta. This study employs a quantitative method with an associative approach and utilizes path analysis to examine direct, indirect, and simultaneous relationships among the research variables. The data were collected through questionnaires distributed to 25 respondents consisting of employees and management of BPR Artatama Sejahtera, South Jakarta. Data analysis was conducted using statistical tests, including partial effect tests, simultaneous effect tests, and moderation tests. The results indicate that operational efficiency has a positive and significant effect on Good Corporate Governance. Risk management also has a positive and significant effect on GCG. Furthermore, Good Corporate Governance is proven to have a positive effect on corporate profitability. Profitability acts as a moderating variable that strengthens the relationship between operational efficiency and Good Corporate Governance, as well as the relationship between risk management and Good Corporate Governance.